EXPANSION OF THE RESOURCE BASE OF COMMERCIAL BANKS (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, the resource base of commercial banks, its structural elements have been studied, the analysis of the resource base of commercial banks operating in our country has been carried out, and suggestions have been made on ways to optimize it.